An algorithm development environment for problem-solving: software review - Chen, Xianshun (Memetic computing, 2012)
Algorithm Development Environment for Problem Solving (ADEP) is a development platform catering to the needs of designing and exploring computationally viable configurations of metaheuristic algorithms. It is motivated by the lack of tools capable of capitalizing on the richness of memetic computing techniques that surfaced in recent years. This software review article introduces the functional features of ADEP and describes the the various utility modules within the ADEP metaheuristics framework, in particular the LVRP tree data structure, configuration and simulation visualization, and the automated configuration via the problem-driven learning engine.